Exploring the Evolution of Personal Learning Environments: A Thematic Review - Karimi, Amir (Journal of Teaching and Learning, 2026)
This manuscript presents a bibliometric analysis of personal learning environments (PLEs) over 25 years, drawing on 494 documents from 318 sources. Three scientometric software programs were used in data analysis: VOSviewer, Bibliometrix, and Publish & Perish. It reveals a steady growth in the field, with an average annual increase of 5.7% in publications and an average document age of 8.9 years, indicating a blend of current and historical research. Spanish universities stood out as leading institutions in PLE research, suggesting Spain's pivotal role in advancing the field, possibly due to funding, policy, or a robust scientific community. Spain ranked first in the frequency of contributions to PLE research, followed by Italy, Portugal, Finland, Switzerland, and France. Two influential publications in e-learning were highlighted: interactive learning environments from the UK and digital education review from Spain. New and fundamental keywords and emerging research areas were identified and categorized into leading clusters and types. This process enhances the understanding of the subject matter and facilitates the exploration of novel avenues for future inquiry. The research findings will be helpful for educational researchers and policymakers.